LOKASI POTENSIAL SIMPUL PERSINGGAHAN TRANSPORTASI MENJADI PUSAT PERMUKIMAN PADA KORIDOR KOTA BENGKULU-PERBATASAN SUMATERA SELATAN - Eko Budi Santoso; Annisa Rahmadanita (Jurnal Ilmiah Wahana Bhakti Praja, 2021)
The Bengkulu Province area is traversed by a primary arterial road that functions as a development axis that connects Bengkulu City with Palembang City, through Lubuk Linggau City, Rejang Lebong Regency, Kepahiang Regency, and Central Bengkulu Regency. The existence of the national primary arterial road corridor as the axis of development is often neglected in regional development. This research is in order to take advantage of the existence of the development axis corridor area, by identifying where are the potential locations of transportation stopover nodes (SPT) that are possible to be developed and which have high potentiality rankings to be developed into residential centers along the Bengkulu City-South Sumatra Border corridor? The research method is descriptive qualitative. Researchers try to photograph the real conditions that exist in the field by including authentic evidence from various data collection techniques carried out, by basing inhibition based on predetermined indicators based on Development Axes theory (Pottier, 1963 in Hilhorst, 1972) and SPT development theory on SP (Santoso, 2014). The conclusion of this study is that in the Bengkulu City-BTS primary arterial road corridor, South Sumatra (Lubuk Linggau), there are 48 potential locations for the development of the SPT into a Settlement Center (which is bigger) with 28 functional and 20 potential. In the Bengkulu City area, there are 5 potential locations with 4 functional and 1 location is still potential. In Bengkulu Tengah Regency, there are 23 potential locations with 14 functional and 10 potential. In Kepahiang Regency, there are 7 potential locations with 4 functional and 3 potential. In Rejanglebong Regency there are 15 potential locations, with 9 functional and 6 potential. As for recommendations related to differences in the development and functionality of potential locations, Regency/City and Provincial Governments need to develop different strategies for each type of potential location related to existing developments and weaknesses. Keywords: Potential Location, Transportation Stopover Node, Settlement Center